The status of Vitamin D in medical students in the preclerkship years of a Saudi medical school - Abdulmohsen H Al-Elq (Wolters Kluwer Medknow Publications, 2012)
Background : The prevalence of vitamin D deficiency has recently been recognized in different parts of the world, even affecting healthy populations. The deficiency of vitamin D can lead to rickets in children and osteomalacia in adults. Few studies have been done to evaluate the status of vitamin D in the medical community. The objective of this study was to evaluate the prevalence of low levels of vitamin D in healthy Saudi medical students. Materials and Methods: A cross-sectional study was carried out in November 2009 on male and female students in the preclerkship years of medical school at the King Faisal University, Dammam. Data on age, consumption of dairy products and seafood, and exposure to sunlight were collected. The body mass index was calculated. Approximately, 15 ml of blood was extracted for the measurement of serum calcium, serum albumin, serum phosphorus, alkaline phosphatase, fasting parathyroid hormone, and vitamin D levels. Vitamin D deficiency was defined as serum 25-hydroxy vitamin D < 50 nmol/l. Comparison between groups was done for statistical significance using an unpaired t-test. Significance was set at P < 0.05 using 95% CI for all comparisons. Results: The data from 95 male and 103 female students were analyzed. The mean age for all students was 19.54 years. In 100% of the students, the vitamin D level was low. The prevalence of vitamin D deficiency in all students was 96.0% (92.64% in males and 99.03% in females), while the remaining 4% had vitamin D insufficiency. The mean 25-hydroxy vitamin D level was 26.83 ± 12.60 nmol/l in males and 16.03 ± 8.28 nmol/l in females (P-value = 0.0001). Males had a statistically significant higher body mass index as well as consumption of dairy products, while the consumption of seafood was significantly higher in females. There was no difference between the two groups in terms of exposure to the sun. Conclusion: Vitamin D deficiency was highly prevalent among medical students included in this study. An urgent action has to be taken in order to prevent adverse consequences of low vitamin D in the young, otherwise healthy populations.